ANALISIS NILAI INDEKS KEANDALAN SISTEM JARINGAN DISTRIBUSI UDARA 20 KV PADA PENYULANG PANDEAN LAMPER 1,5,8,9,10 DI GI PANDEAN LAMPER - Arifani, Nur Indah; Winarno, Heru (Vocational School Diponegoro University, 2013)
Nur Indah Arifani, Heru Winarno, in this paper explain that interruption of electricity supply for customers is very disturbing activity. Interruption/outage that occurred in the distribution network led to the disruption of continuity of service. Lots and duration of outages at the feeder Pandean Lamper 1,5,8,9, and 10 at Substation Pandean Lamper observed by the authors to get a reliability index value. This observation aims to get the value of SAIFI and SAIDI in substation feeder PDL Pandean Lamper at 1, 5, 8, 9, 10 and compared with a standard value of PLN as a world-class company (WCC) is SAIFI = 3 time/customer/year, SAIDI = 1.66 hours/customer/year. Disorders due to components and equipment as well as the tree is the most dominant cause of the outage. To obtain this index takes a data rate of failure (λ), a long interruption (U) and the number of customers (N) as well as get other customer-oriented index values ​​are CAIFI, CAIDI, ASAI, ASUI. The analysis showed that the reliability index value for the feeder SAIFI value of PDL 1, 5, 8, 9, 10 all have a lower index value of PLN standards. For the fifth feeder SAIDI value only feeder PDL 9 impaired outages longer than four other feeder with an index value of 1.78 hours/customer/year beyond the PLN standard. For those who do not fit the standard feeder PLN performed maintenance measures components, as well as the supervision of the disturbance and other animals. Keywords: distribution network, continuity, blackouts, interruption, SAIFI, SAIDI, CAIFI, CAIDI.